Report on workshop on high performance computing and communications for grand challenge applications: computer vision, speech and natural language processing, and artificial intelligence - Wah, B.W.; Huang, T.S.; Joshi, A.K.; Moldovan, D.; Aloimonos, J.; Bajcsy, R.K.; Ballard, D.; DeGroot, D.; DeJong, K.; Dyer, C.R.; Fahlman, S.E.; Grishman, R.; et al. (IEEE transactions on knowledge and data engineering, 1993)
The findings of a workshop, the goals of which were to identify applications, research problems, and designs of high performance computing and communications (HPCC) systems for supporting applications are discussed. In computer vision, the main scientific issues are machine learning, surface reconstruction, inverse optics and integration, model acquisition, and perception and action. In speech and natural language processing (SNLP), issues were identified statistical analysis in corpus-based speech and language understanding, search strategies for language analysis, auditory and vocal-tract modeling, integration of multiple levels of speech and language analyses, and connectionist systems. In AI, important issues that need immediate attention include the development of efficient machine learning and heuristic search methods that can adapt to different architectural configurations, and the design and construction of scalable and verifiable knowledge bases, active memories, and artificial neural networks.< >